AI-Supported English Language Learning: Indonesian Teacher Perspectives and Implementation - Rohman, Kholilur; Subarjo, Subarjo; Elfiyanto, Sonny; Karimullah, Imam Wahyudi (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This research explores English teachers’ perceptions and experiences in integrating Artificial Intelligence (AI) tools into primary and secondary English language instruction. Using a qualitative narrative approach, data were collected through semi-structured interviews with six teachers across educational levels. The findings reveal that teachers generally perceive AI positively, recognizing its potential to enhance student engagement, provide personalized feedback, and support the development of vocabulary, grammar, speaking, reading, and writing skills. Tools such as Quizizz, Grammarly, ChatGPT, and Google Assistant were found to foster learner autonomy and confidence. However, challenges persist, including limited infrastructure, time constraints, and varying levels of digital literacy. Teachers also expressed concerns about overreliance on AI, reduced critical thinking, and diminished student originality. The research concludes that while AI offers valuable pedagogical support, its effective integration requires thoughtful planning, ethical awareness, and institutional backing.